Collagen Fiber‐Based Advanced Separation Materials: Recent Developments and Future Perspectives. Issue 46 (27th February 2022) - Xiao, Hanzhong; Wang, Yujia; Hao, Baicun; Cao, Yiran; Cui, Yiwen; Huang, Xin; Shi, Bi
Abstract: Separation plays a critical role in a broad range of industrial applications. Developing advanced separation materials is of great significance for the future development of separation technology. Collagen fibers (CFs), the typical structural proteins, exhibit unique structural hierarchy, amphiphilic wettability, and versatile chemical reactivity. These distinctive properties provide infinite possibilities for the rational design of advanced separation materials. During the past 2 decades, many progressive achievements in the development of CFs‐derived advanced separation materials have been witnessed already. Herein, the CFs‐based separation materials are focused on and the recent progresses in this topic are reviewed. CFs widely existing in animal skins display unique hierarchically fibrous structure, amphiphilicity‐enabled surface wetting behaviors, multi‐functionality guaranteed covalent/non‐covalent reaction versatility. These outstanding merits of CFs bring great opportunities for realizing rational design of a variety of advanced separation materials that were capable of achieving high‐performance separations to diverse specific targets, including oily pollutants, natural products, metal ions, anionic contaminants and proteins, etc. Besides, the important issues for the further development of CFs‐based advanced separation materials are also discussed. Abstract : Collagen fibers (CFs), the structural proteins ubiquitously existing in animal skins, feature unique hierarchically fibrous structure, amphiphilicity‐enabled surface wetting behaviors, and versatile reactivity. Owing to the intrinsic merits of CFs, progressive successes have been achieved in developing CFs‐based advanced separation materials. This review provides a comprehensive overview of the recent development of CFs‐based separation materials and their future perspectives.